Annual Plan for the Year 1972-73 Maharashtra Government - Planning Commission (Planning Commission, 1972)
The economy in Maharashtra State has been affected by two successive scarcity years. Adverse climatic conditions during 1970-71 and unfavorable monsoon in 1971-72 have adversely affected agricultural production in the State. Government had declared scarcity in about 15,000 villages in 20 districts of the State in 1971-72. Industrial production however showed a slight recession. General index number of Industrial production in India increased by 4 9 per cent in 1970 over the previous year. In the case of Maharashtra the growth in 1970 of some important industries is significant; in the case of sugar industry, the growth was 10’9 per cent, chemicals 8'7per cent, electrical machinery 10’5 per cent, petroleum 5-9 per cent and machinery other than electrical machinery 5'8 per cent. There was no increase in production of textiles.
Maharashtra Government